Reformulation Strategies in The King’s Ankus, a Chapter from Rudyard Kipling’s The Jungle Book - Zúñiga, María Carolina (Íkala, Revista de Lenguaje y Cultura, 2015)
The objective of this article was to identify the reformulation strategies used in the adaptation of The King's Ankus, a chapter from Rudyard Kipling's The Jungle Book. A comparative analysis was conducted on two different editions: the hypotext (19--) and the hypertext (2006). 260 modifications were identified, and 56% correspond to reductions, 38% to variations and only 6% to expansions. The new target readers and different context of reception produce cultural changes in the text that should be relevant for translation and children and young adult´s literature.